2004
DOI: 10.1016/j.ces.2004.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous heat-flow differential calorimetry and thermogravimetry for fast determination of sorption isotherms and heat of sorption in environmental or food engineering

Abstract: A new experimental technique is described for the determination of desorption characteristics for engineering purposes. A TGA-DSC set-up is used in isothermal mode to achieve the thermal desorption of deformable standard materials like microcrystalline cellulose and kaolin in dry air. Assumptions on heat and mass transfer are made and discussed in order to derive desorption isotherms and heat of sorptions from the calorimetric and gravimetric signals. The method is rapid and accurate for high-temperature desor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 19 publications
(19 reference statements)
1
11
0
Order By: Relevance
“…Furthermore, the selection of threshold temperature is essentially important since it is used for distinguishing the free and bound water . As a result, DTA or DSC performed simultaneously with Thermogravimetric analysis (TGA) (aslo known as TG-DTA and TG-DSC), as proposed by Chen et al (1997) and Ferrasse & Lecomte (2004), for biological products.…”
Section: Water Classification and Measurement Techniquesmentioning
confidence: 99%
“…Furthermore, the selection of threshold temperature is essentially important since it is used for distinguishing the free and bound water . As a result, DTA or DSC performed simultaneously with Thermogravimetric analysis (TGA) (aslo known as TG-DTA and TG-DSC), as proposed by Chen et al (1997) and Ferrasse & Lecomte (2004), for biological products.…”
Section: Water Classification and Measurement Techniquesmentioning
confidence: 99%
“…This value can be obtained from water sorption isotherms recorded at different temperatures based on the Clausius-Clapeyron equation, see later Modeling section (Sirota 1987). However, it was reported that the use of sorption isotherms were associated with experimental difficulties for low and high water activity due to the limitation in the use of saturated salts (Ferrasse and Lecomte 2004). A second method to evaluate the desorption energy is by means of calorimetric techniques (Rü ckold et al 2003;Hatakeyama et al 2000;Mulet et al 1999;Sá nchez et al 1997;Zang and Sapieha 1991;Fielden et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The total heat of sorption is derived from the calorimetric signal and the mass loss (Ferrasse and Lecomte, 2004). As can be seen on Figure 2, the isosteric heat of sorption can be neglected for 2 .…”
Section: Total Heat Of Desorptionmentioning
confidence: 99%
“…A fast transient method was elaborated and tested for a large range of products (Ferrasse and Lecomte, 2004;Arlabosse et al, 2003). This method, using a thermogravimetric analyzer (TGA) coupled with a differential scanning calorimeter DSC111 (Setaram, Caluire, France) in isothermal mode, was successfully applied to sludge description.…”
Section: Sorption Isothermmentioning
confidence: 99%